Документи сімейної історії мецената Г.С. Тарновського - Товстоляк, Н.М. (Сіверщина в історії України, 2020)
Стаття побудована на маловідомих документах і новій інформації про сімейну історію українського мецената, поміщика і підприємця Григорія Степановича Тарновського (1790–1853). На основі майнових документів родинного архіву Тарновських, листів їх сучасників встановлено, що власником садиби Качанівка Г.С. Тарновський став у 1816 р. за заповітом його вітчима Г.Я. Почеки. У статті наведено невідомі факти про його дружину Ганну Дмитрівну Тарновську (1798–1853) та її родичів – знаменитих катеринославських дворян Алексєєвих. Її батько, Д.Л. Алексєєв, – багатий поміщик Півдня України, власник садиби Котівка, мав ступінь доктора Оксфордського університету. Сім’ї дворян Алексєєвих і Тарновських дружили, в 1820–1830 рр. Д.Л. Алексєєв і його зять Г.С. Тарновський одночасно розбудовували свої садиби (чудові будинки і парки); ними було зібрано великі бібліотеки, колекції живопису, антикваріату, історичних цінностей. У першій половині ХІХ ст. Г.С. Тарновський став засновником знаменитого культурного центру в Качанівці; його маєтки стали економічно розвиненими господарствами. Він був меценатом у мистецтві, живописі, музиці. The article have been based on a little known documents and new information about family history of Ukrainian philanthropist, landowner and owner of a business Hryhorii Stepanovych Tarnovskyi (1790–1853). On the base of property documents of Tarnovskyi’s family archive, their contemporaries letters, it was ascertain that H.S. Tarnovskyi became of Kachanivka Estate owner in 1816 by his stepfather H.Ya. Pocheka’s testament. In this article provides unknown information about his wife – Hanna Dmytrivna Tarnovska (1798–1853) and her family, well– known Katerinoslav nobles Aleksieiev. His father, D.L. Aleksieiev, – rich landowner of Ukrainian South, owner of Kotivka Estate, he was a Doctor of Science of Oxford Univ ersity. Noble family Aleksieiev and family Tarnovskyi were friends, in 1820–1830 D.L. Aleksieiev and his son–in–law H.S. Tarnovskyi built their Estate at the same time: there were beautiful manor–houses and parks. In H.S. Tarnovskyi’s Kachanivka Estate and D.L. Aleksieiev’s Kotivka Estate they completed great libraries, collections of paintings, antiquary, historical valuables. At the first part of 19th centure H.S. Tarnovskyi was founder of famous cultural centre in his Kachanivka. There were economic developed farms and plants in his Estates. He was philanthropist of arts, poets and musicians. H.S. Tarnovskyi had an orchestra at Kachanivka which was the first to play some of the musical pieces, created by M.I. Hlynka in Kachanivka. The Kachanivka Estate was visited famous Ukrainian poet and painter, friend of Tarnovsky’s family T.H. Shevchenko.